1990
DOI: 10.1002/crat.2170250706
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and molecular structures of N‐alkyl‐N, N‐dimethyl‐3‐(heptamethyltrisiloxan‐3‐yl) propylammonium bromides

Abstract: Die Kristallstruktur von C, ,H40N02Si3Br wurde durch Verfeinerung des aus der Strukturbestimmung von C16H42N02Si3Br iibernommenen Strukturmodells mit einem R-Wert von 0.099 bestimmt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The mechanism for this reduction is unknown; but it must be induced by the interactions with SiO 2 surface or a genuine property of the CPL liquid/air interface. Various quaternary ammonium halides containing siloxane surfactant compounds have also shown a small degree of reduction in water. It was also reported that some halide counterions could be coordinated by multiple nitrogen groups or replaced by water molecules. , Similar reduction processes might take place during the deposition of CPL (spin-coating from aqueous solution).…”
Section: Resultsmentioning
confidence: 98%
“…The mechanism for this reduction is unknown; but it must be induced by the interactions with SiO 2 surface or a genuine property of the CPL liquid/air interface. Various quaternary ammonium halides containing siloxane surfactant compounds have also shown a small degree of reduction in water. It was also reported that some halide counterions could be coordinated by multiple nitrogen groups or replaced by water molecules. , Similar reduction processes might take place during the deposition of CPL (spin-coating from aqueous solution).…”
Section: Resultsmentioning
confidence: 98%
“…The ethyl group may be disordered at room temperature, but it was impossible to resolve separate positions for C6. The position of C6 is different from the corresponding positions of this atom in dialkyldimethylammonium bromides (Taga, Machida, Kimura, Hayashi, Umemura & Takenaka, 1986Taga, Miwa, Machida, Kimura, Hayashi, Umemura & Takenaka, 1990), in N-alkyl-N,N-dimethyl-3-(heptamethyltrisilox-an-3-yl)-l-propanaminium bromide (Ramm, Schulz, Sonnek & Schmaucks, 1990) and in 1,3,3,5,5,5 -heptamethyltrisiloxan-1 -yl)-1-propanaminium bromide (Rudert & Schmaucks, 1994a). The title compound has a C3--N4--C5---C6 torsion angle of 178.0(4) ° , whereas the above cited compounds have corresponding torsion angles between 50.2 and 57.…”
mentioning
confidence: 97%